2006
DOI: 10.1074/jbc.m510771200
|View full text |Cite
|
Sign up to set email alerts
|

Temperature-dependent Biosynthesis of 2-Thioribothymidine of Thermus thermophilus tRNA

Abstract: 2-Thioribothymidine (s 2 T) is a modified nucleoside of U, specifically found at position 54 of tRNAs from extreme thermophilic microorganisms. The function of the 2-thiocarbonyl group of s 2 T54 is thermostabilization of the three-dimensional structure of tRNA; however, its biosynthesis has not been clarified until now. Using an in vivo tRNA labeling experiment, we demonstrate that the sulfur atom of s 2 T in tRNA is derived from cysteine or sulfate. We attempted to reconstitute 2-thiolation of s 2 T in vitro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
81
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 75 publications
(86 citation statements)
references
References 43 publications
5
81
0
Order By: Relevance
“…This observed effect is probably caused by the reinforcement of the U54-A58 tertiary base pair. The m 1 A58 modification is a positive determinant for the 2-thiouridylation complex (TtuA, TtuB, TtuC, and the other protein factors), which catalyzes s 2 U54 formation (8,9). Therefore, our current results and other reports (8,9) (47), we found that the Arg-97, Lys-282, and Lys-287 residues in TrmFO are important for the methyl transfer reaction.…”
Section: Trmfo Can Distinguish the T-arm From The Anticodon Arm In Tmentioning
confidence: 99%
See 1 more Smart Citation
“…This observed effect is probably caused by the reinforcement of the U54-A58 tertiary base pair. The m 1 A58 modification is a positive determinant for the 2-thiouridylation complex (TtuA, TtuB, TtuC, and the other protein factors), which catalyzes s 2 U54 formation (8,9). Therefore, our current results and other reports (8,9) (47), we found that the Arg-97, Lys-282, and Lys-287 residues in TrmFO are important for the methyl transfer reaction.…”
Section: Trmfo Can Distinguish the T-arm From The Anticodon Arm In Tmentioning
confidence: 99%
“…The m 1 A58 modification is a positive determinant for the 2-thiouridylation complex (TtuA, TtuB, TtuC, and the other protein factors), which catalyzes s 2 U54 formation (8,9). Therefore, our current results and other reports (8,9) (47), we found that the Arg-97, Lys-282, and Lys-287 residues in TrmFO are important for the methyl transfer reaction. Based on the current and previous experimental results, we constructed the docking model of TrmFO and T-arm of yeast tRNA Phe (Fig.…”
Section: Trmfo Can Distinguish the T-arm From The Anticodon Arm In Tmentioning
confidence: 99%
“…In Thermus thermophilus, inactivation of TrmI induces a thermosensitive phenotype (Droogmans et al 2003). Since TrmI disruption strongly reduced 2-thiolation of 5-methyl-2-thiouridine (s 2 T) at position 54 (Shigi et al 2006b), the decreased thermo-tolerance observed in the DTrmI strain can be partly explained by the lack of 2-thiolation of s 2 T54, a key modification required for tRNA thermostability (Yokoyama et al 1987;Shigi et al 2006a).…”
Section: Introductionmentioning
confidence: 99%
“…, and 2-methylthio-N6-alkyladenosine (2). Most of these modifications are found in transfer RNA (tRNA), where they have various important cellular roles, such as controlling the fidelity of translation (3)(4)(5), recognizing aminoacyltRNA synthetase (6), sensing UV radiation stress (7), and stabilizing the ternary structure of tRNA for growth at high temperatures (8)(9)(10).…”
mentioning
confidence: 99%